Bedside dressing changes for open abdomen in the intensive care unit is safe and time and staff efficient. Issue 1 (December 2016) - Seternes, Arne; Fasting, Sigurd; Klepstad, Pål; Mo, Skule; Dahl, Torbjørn; Björck, Martin; Wibe, Arne
Abstract Background Patients with an open abdomen (OA) treated with temporary abdominal closure (TAC) need multiple surgical procedures throughout the hospital stay with repeated changes of the vacuum-assisted closure device (VAC changes). The aim of this study was to examine if using the intensive care unit (ICU) for dressing changes in OA patients was safe regarding bloodstream infections (BSI) and survival. Secondary aims were to evaluate saved time, personnel, and costs. Methods All patients treated with OA in the ICU from October 2006 to June 2014 were included. Data were retrospectively obtained from registered procedure codes, clinical and administrative patients' records and the OR, ICU, anesthesia and microbiology databases. Outcomes were 30-, 60- and 90-day survival, BSI, time used and saved personnel costs. Results A total of 113 patients underwent 960 surgical procedures including 443 VAC changes as a single procedure, of which 165 (37 %) were performed in the ICU. Nine patients died before the first scheduled dressing change and six patients were closed at the first scheduled surgery after established OA, leaving 98 patients for further analysis. The mean duration for the surgical team performing a VAC change in the ICU was 63.4 (60.4–66.4) minutes and in the OR 98.2 (94.6–101.8) minutes (p  < 0.001). The mean duration for the anesthesia team in the OR was 115.5 minutes, while this team was not used in the ICU. Personnel costs were reduced by €682 per procedure when using the ICU. Forty-two patients had all the VAC changes done in the OR (VAC-OR), 22 in the ICU (VAC-ICU) and 34 in both OR and ICU (VAC-OR/ICU). BSI was diagnosed in eight (19 %) of the VAC-OR patients, seven (32 %) of the VAC-ICU and eight (24 %) of the VAC-OR/ICU (p  = 0.509). Thirty-five patients (83 %) survived 30 days in the VAC-OR group, 17 in the VAC-ICU group (77 %) and 28 (82 %) in the VAC-OR/ICU group (p  = 0.844). Conclusions VAC change for OA in the ICU saved time for the OR team and the anesthesia team compared to using the OR, and it reduced personnel costs. Importantly, the use of ICU for OA dressing change seemed to be as safe as using the OR.